2021
DOI: 10.1097/wnr.0000000000001716
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in type 2 diabetes patients with and without diabetic peripheral neuropathy: a mismatch negativity study

Abstract: ObjectivesTo assess the cognitive impairment in patients with type 2 diabetes mellitus (T2DM) using mismatch negativity (MMN) and to explore the relationship between cognitive impairment and diabetic peripheral neuropathy (DPN).Methods Sixty-six T2DM patients and 40 healthy controls were included. For each participant, mini-mental state examination (MMSE) was applied to assess the general cognitive function and MMN was elicited. T2DM patients were divided into two subgroups: subgroup DPN−, patients without DPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…56 Moreover, the risks between DPN and cognitive dysfunction are shared, and encompass both glucose and lipid centric mechanisms. 54,55 In clinical studies of patients with T1D and T2D, DPN is a risk for poorer cognitive function 57,58 and brain structural changes. 59 The possibility of shared or similar neurological damage in the periphery and centrally in diabetes is intriguing and the increasing burden of diabetes has implications for the future burden of dementia.…”
Section: Dpn and Cognitive Declinementioning
confidence: 99%
“…56 Moreover, the risks between DPN and cognitive dysfunction are shared, and encompass both glucose and lipid centric mechanisms. 54,55 In clinical studies of patients with T1D and T2D, DPN is a risk for poorer cognitive function 57,58 and brain structural changes. 59 The possibility of shared or similar neurological damage in the periphery and centrally in diabetes is intriguing and the increasing burden of diabetes has implications for the future burden of dementia.…”
Section: Dpn and Cognitive Declinementioning
confidence: 99%
“…m 6 A methylation is biased toward neuronal transcripts and is sensitive to neuronal activity [21]. In the hippocampus, m 6 A regulates several developmental and physiological processes, including neurogenesis, axonal growth, synaptic plasticity, circadian rhythms, cognitive function, and stress response [22]. With continuous progress in high-throughput sequencing technology, increasing attention to the m 6 A landscape has been focused on neoplastic and non-neoplastic diseases of the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Manschot and co-workers [ 113 ] concluded that peripheral diabetic neuropathy, assessed by measuring pain, touch, and vibratory sensation, was not related to cognitive functions or brain abnormalities (in the form of white matter lesions and cortical and subcortical atrophy) when analyzed by magnetic resonance imaging. However, a recent study observed that CI was more common among diabetic patients regardless of the presence of peripheral neuropathy [ 49 ], although those with DM did have more severe cognitive dysfunctions. Accordingly, the pathophysiology of diabetic peripheral neuropathy and CI seem to share underlying mechanisms such as insulin dysregulation, inflammation, oxidative stress, and advanced glycation end products, as also suggested by some other authors [ 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have shown that type 2 DM is associated with CI in older adults [ 43 , 44 , 45 ], with the reported detection of reduced reasoning speed [ 46 , 47 ], memory [ 46 , 48 ], and executive functions in these patients [ 47 , 48 ]. Some work [ 49 , 50 ] has examined the relationships between peripheral and central nervous system damage in diabetic patients. However, the exploration of sensory functions has not yet been explored in depth, and many aspects of this field still require clarification.…”
Section: Introductionmentioning
confidence: 99%